Adaptive Integrated Guidance and Control Based on Backstepping for the Landing of Reusable Launch Vehicles*. Issue 28 (2015) - Yan, Han; He, Yingzi
Abstract: Based on the idea of reference-trajectory guidance, an integrated guidance and control (IGC) design approach is proposed for the landing of a reusable launch vehicle (RLV) by using backstepping and adaptive control. The nonlinear IGC model for the landing phase is formulated, and in order to handle the influence of the nonlinearity term, an adaptation law is introduced into the backstepping scheme to design an IGC law that can make flight path angle robustly track its reference value and keep the heading angle near zero (heading to the runway). Comparing with the existing guidance and control methods, the IGC law designed in this paper can guarantee the stability of the overall system that composed of guidance and control systems, and the law also has robustness with respect to uncertainties. The numerical simulation confirms the effectiveness of the proposed design approach.